Modeling Of Digital Media In The Management Of Educational Performance In Morocco School’s - Abderrazak Mazouak; Mustapha Bassiri; Imad Lamniai; Jaouad Muftisada; Malika Tridane; Said Belaaouad (Iraqi Journal of Science, 2021)
Faced with the increasing opening of the education and training sector on the digital world, the actors of this sector are called to develop alongside the disciplinary and pedagogical skills other strategic and technological skills that allow to offer the adequate conditions to manage their establishments.Today, the pedagogical director is called to master an important set of technical and technological tools and this for two complementary reasons, the first is the knowledge of educational and pedagogical and the second is innovation in managerial practicesOur intervention is part of a comparative approach in which we will verify the degree of use of technological tools by our population of directors (123) private and publicThen, we will try to model the different IT tools and check their impact on managerial practices.Finally, we point out all the human, technical, social and cultural constraints that hinder the process of the integration of ICT in managerial practices by proposing a set of suggestions likely to attach the motivation and will of managers in technology. of their practices